Réponses

2014-01-28T15:14:50+01:00
Bonjour
A= (x+4) (x-6) + (-1+x) (x+7)
x² -6x +4x -24 -x -7 +x² +7x
2x² +4x - 31

B= ( x-1 ) (5x - 2) - ( -6+3x (-1+x)
5x² -2x -5x +2 - (6 -6x -3x +3x²)
5x² -7x +2 -6 +6x +3x -3x²
2x² +2x -4

C= - (3x-8) (x+4) - (7x-8) (-1+7x)
- ( 3x² + 12x - 8x - 32) - ( -7x +49x² +8 - 56x)
- ( 3x² +4x -32) - (-63x +49x² +8 )
-3x² -4x +32 +63x -49x² -8
-52x² + 59x +24

D= - (2x-5) (3-4x) + (6x-9)  (-2x-1)
- (6x - 8x² -15 + 20x -12x² -6x +18x -9)
-6x +8x² +15 -20x +12x² +6x -18x +9
20x² -38x +24